Implementasi Speech Recognition untuk Asisten Virtual dengan Python - Yulius Setyawan; Yo Ceng Giap (ALGOR, 2022)
The most common way of communicating used by humans is by voice or speech. Many experiments were carried out in the aspect of sound processing to create a mechanical model that simulates how humans communicate verbally. Voice recognition technology aims to develop systems and techniques on how to introduce voice commands so that they can be understood by machines so that machines are able to carry out the commands given. This study uses speech recognition technology to be implemented into a desktop-based personal virtual assistant application to help simplify daily tasks through a computer. The results of this study resulted in speech recognition to perform certain general tasks on the desktop and turn on electronic devices. From the tests that have been carried out, the application can recognize voice commands to carry out the given commands and can turn on or turn off electrical devices as expected.